2019
DOI: 10.1080/21691401.2019.1652625
|View full text |Cite
|
Sign up to set email alerts
|

Methylation dependent microRNA 1285-5p and sterol carrier proteins 2 in type 2 diabetes mellitus

Abstract: View related articles View Crossmark data Citing articles: 2 View citing articles Methylation dependent microRNA 1285-5p and sterol carrier proteins 2 in type 2 diabetes mellitus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…miRNAs are believed to be the most important dictatorial molecules in the cells and controlling broad variety of cellular functions such as proliferation, migration, invasion, and apoptosis (Sekar et al, 2016a(Sekar et al, , 2016bBai et al, 2019). miRNAs interact with the mRNAs at the post-transcriptional levels and regulate the gene expression by either repression or degradation of the translation mechanisms.…”
Section: Clinical Perspective and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…miRNAs are believed to be the most important dictatorial molecules in the cells and controlling broad variety of cellular functions such as proliferation, migration, invasion, and apoptosis (Sekar et al, 2016a(Sekar et al, , 2016bBai et al, 2019). miRNAs interact with the mRNAs at the post-transcriptional levels and regulate the gene expression by either repression or degradation of the translation mechanisms.…”
Section: Clinical Perspective and Future Directionsmentioning
confidence: 99%
“…Recent research suggested that miRNAs are potential biomarkers in both communicable and noncommunicable diseases (Sekar et al, 2016a(Sekar et al, , 2016bBai et al, 2019;Humphries et al, 2019;Li et al, 2019). In contrast, in the case of mitochondrial dysfunction in miRNAs, the number of studies and investigations are comparatively less than those of other diseases and dysfunctions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A wide variety of pre-polymerised polymethyl methacrylate (PMMA) blocks have been introduced on the market based on further studies related with nanoparticles and data was produced on surface roughness [11]. Our team has extensive knowledge and research experience that has translated into high quality publications [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Open Accessmentioning
confidence: 99%
“…The prepared surface is etched with 37% o-phosphoric acid for 15-20 seconds and the bonding agent is a applied and cured for 20 seconds, followed by restoring the cavity with filled resin and the adjacent unaffected pits and fissure is sealed using a Dental Pit & Fissure Sealant [14]. Our team has extensive knowledge and research experience that has translate into high quality publications [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%